2018
DOI: 10.3390/electronics7120394
|View full text |Cite
|
Sign up to set email alerts
|

A Torque Vectoring Control for Enhancing Vehicle Performance in Drifting

Abstract: When dealing with electric vehicles, different powertrain layouts can be exploited. Among them, the most interesting one in terms of vehicle lateral dynamics is represented by the one with independent electric motors: two or four electric motors. This allows torque-vectoring control strategies to be applied for increasing vehicle lateral performance and stability. In this paper, a novel control strategy based on torque-vectoring is used to design a drifting control that helps the driver in controlling the vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Phase portrait analysis has proved to be a very effective tool for analyzing the dynamics of a nonlinear system as it immediately reveals the location and type of equilibria in the system and the region of attraction, or stable regions, about those equilibria. [18,29,31] showed that the fundamental planar instabilities critical to control problems such as ESP or stabilizing a drifting vehicle arise from the yaw and sideslip dynamics.…”
Section: Phase Portraitmentioning
confidence: 99%
See 4 more Smart Citations
“…Phase portrait analysis has proved to be a very effective tool for analyzing the dynamics of a nonlinear system as it immediately reveals the location and type of equilibria in the system and the region of attraction, or stable regions, about those equilibria. [18,29,31] showed that the fundamental planar instabilities critical to control problems such as ESP or stabilizing a drifting vehicle arise from the yaw and sideslip dynamics.…”
Section: Phase Portraitmentioning
confidence: 99%
“…where on the left side the obtained control actions are the combined ones while on the right side the control actions provided by the PIs controllers are present. η are the efficiency factors that weights the controller action in combined control which are obtained by weighting the performance indexes as in equation (18).…”
Section: Control Strategymentioning
confidence: 99%
See 3 more Smart Citations